Evaluation of General Educational Hospitals Affiliated to Mashhad University of Medical Sciences Based on the Standards of Health-promoting Hospitals - Shaghayegh Yousefi; Ali Vafaeenajar; Habibollah Esmaily; Elaheh Hooshmand (Iranian Association of Health Education and Health Promotion, 2017)
Background &Objective: Global changes have created new health challenges specifically in hospitals. In the new perspective, nowadays hospitals are the best places for health promotion and preventive services. The present study aimed to evaluate the performance of general educational hospitals of Mashhad University of Medical Sciences based on the standards of health promoting hospitals. Materials & Methods: The present study was a descriptive - analytic and the data collection tool was a World Health Organization questionnaire regarding the standards of health promoting hospitals. To fill in the questionnaires, a team of main members of the hospitals was formed and standards assessment criteria were determined, then the questionnaires were completed by each team member. The data analysis was performed by SPSS software through statistical indicators (mean, SD), t-test and paired t-test.   Results: The results were identified by five categories of activities based on the standards of health promotion hospitals. Regarding standards, the highest score was related to patient's information and therapeutic interventions (78) and the lowest was for managerial policies (51.1). In total, all hospitals were in the same situation to perform the standards of health promotion hospitals, with a mean score of 63.80%. Conclusion: It seems that some activities related to the health-promoting hospitals (HPS) are being carried out in hospitals. Therefore, for improving the quality of health services, encouraging policymakers and healthcare managers to create consistent policies will have an effective role to improve the status of hospitals.